2021
DOI: 10.3390/cells10112867
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A/ANO1: Current Strategies and Novel Drug Approaches for Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is the most common of rare hereditary diseases in Caucasians, and it is estimated to affect 75,000 patients globally. CF is a complex disease due to the multiplicity of mutations found in the CF transmembrane conductance regulator (CFTR) gene causing the CFTR protein to become dysfunctional. Correctors and potentiators have demonstrated good clinical outcomes for patients with specific gene mutations; however, there are still patients for whom those treatments are not suitable and require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 110 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Functionally, anionic channels could be activated by cell volume changes or the changes of intracellular concentrations of proton, InsP4 or Ca 2+ . The Ca 2+ -activated chloride channel named TMEM16A/Ano1 is involved in several pathologies as hypertension, stroke and cancer and was expressed in several cell types in mammalians, including smooth muscle and epithelial cells, as reviewed recently [41][42][43]. Immunostaining and RTqPCR results suggested that this channel could support the Ca 2+ -activated chloride current observed in smooth muscle cells from rat portal veins.…”
Section: Discussion and Perspectivesmentioning
confidence: 95%
See 1 more Smart Citation
“…Functionally, anionic channels could be activated by cell volume changes or the changes of intracellular concentrations of proton, InsP4 or Ca 2+ . The Ca 2+ -activated chloride channel named TMEM16A/Ano1 is involved in several pathologies as hypertension, stroke and cancer and was expressed in several cell types in mammalians, including smooth muscle and epithelial cells, as reviewed recently [41][42][43]. Immunostaining and RTqPCR results suggested that this channel could support the Ca 2+ -activated chloride current observed in smooth muscle cells from rat portal veins.…”
Section: Discussion and Perspectivesmentioning
confidence: 95%
“…Previously, this conductance was characterized and blocked by anthracene-9-carboxylic acid and diphenylamine-2,2 -dicarboxylic acid [9] also reported as inhibitors of TMEM16A channels [22]. Even if the anthracene-9-carboxylic acid was used on TMEM16A channel transfected in HEK-293T cells to define the function of the channel [44], the known antagonists-including anthracene-9-carboxylic acid-were poorly specific yet tested in preclinical trials to become pharmacological drugs [41,45]. Toxins from venoms are used more often as preclinical tools to find pharmacological drugs than therapeutic molecules.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…One candidate channel is the calcium-activated chloride channel TMEM16A (ANO1; in non-humans, Tmem16a/Ano1) [15,16,17]. TMEM16A is present in many different cell types and associated with multiple physiological roles, including epithelial secretion [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Cystic fibrosis, a hereditary disease induced by the dysfunction of cystic fibrosis transmembrane conductance regulator chloride channel, could be benefited from activating ANO1 as an alternative Cl − channel. [ 12 , 13 ] Ca 2+ ‐activated chloride currents in vascular smooth muscle cells are candidates for increasing vascular contractility, outlining ANO1 as a promising target for the treatment of hypertension. [ 14 ] In cancer, ANO1 was originally recognized to be positively expressed in gastrointestinal stromal tumor (GIST) and was more well‐recognized as DOG1 (Discovered On GISTs protein 1).…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 , 20 , 21 ] However, despite these preliminary reports, the exact role and concrete mechanisms of ANO1 in GI cancer progression and TIME regulation remain largely unelucidated, while its linkage with immunotherapy has never been explored. On the other hand, although several inhibitors targeting ANO1 has been developed, [ 13 , 22 ] their potential effectiveness against cancer remain unexplored yet by clinical trials because of the lack of strong preclinical evidence supporting ANO1's value as a promising therapeutic target in cancer.…”
Section: Introductionmentioning
confidence: 99%